Construction and Reconstruction of the Object of Study in Educational Research - Álvarez Hernández, Gabriel Alejandro (2019)
This essay raises the discussion and debate around the construction and reconstruction of the object of study in social and human sciences research, more specific in the educational field. First, as a prelude, a series of reflections on subjective, social and cultural implications as the basis for the conception of a reality are outlined. Subsequently, premises and debates are outlined in relation to modern science of the twentieth century to our times, a review that recovers, among other things, the evolution of thought, rationalism, logic and science design from the Galilean and Aristotelian traditions and its influence on the processes of knowledge construction. Then, it emphasizes the importance of ontology as a principle to respond to reality, and to epistemology as the beginning of conceptual configurations that support the approach to the object of study. Finally, it closes highlighting the contributions of theorists who propose ways of approaching reality and building the object, they say, some emerging epistemological approaches that support the discussion are mentioned.